Analysis of boundary layer sounding data from the FIRE Marine Stratocumulus Project - Schubert, Wayne H., author; Ciesielski, Paul, E., author; McKee, Thomas B., author; Kleist, John D., author; Cox, Stephen K., author; Johnson-Pasqua, Christopher, author; Smith, William L., Jr., author (Colorado State University. Libraries, 1987)
We present an analysis of the boundary layer thermodynamic data obtained by the CLASS radiosonde system during the marine boundary layer experiment on San Nicolas Island in the summer of 1987. The analysis procedure retains the highest possible vertical resolution in the data. Plots of temperature, dew point temperature, potential temperature, equivalent potential temperature and saturation equivalent potential temperature are presented for each of the sixty-nine soundings taken during FIRE. Conditions were mostly cloudy with fifty-five of the sixty-nine soundings being released with stratocumulus overhead. For the fifty-live cloudy soundings, cloud top Jumps of equivalent potential temperature i, and total water mixing ratio r were also determined. Each of these soundings is then represented by a point in the (~11., ~r) plane. Fifteen of these soundings are on the unstable aide of the evaporative instability line, and there appears to be some tendency for break-up under these conditions.
October 1987.
FIRE volume 2 on cover.
Keywords: Atmospheric thermodynamics -- California -- San Nicolas Island -- Charts, diagrams, etc; Upper atmosphere -- California -- San Nicolas Island -- Radiosonde observations; Boundary layer (Meteorology)